1996
DOI: 10.1128/iai.64.12.4946-4951.1996
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14 mediates lipopolysaccharide-induced intercellular adhesion molecule 1 expression in cultured human gingival fibroblasts

Abstract: Intercellular adhesion molecule 1 (ICAM-1) is involved in the accumulation and activation of leukocytes in inflammatory diseases such as periodontitis. As reported previously, ICAM-1 is up-regulated on cultured human gingival fibroblasts (HGF) by exposure to lipopolysaccharide (LPS), suggesting a specific LPS recognition mechanism. We therefore investigated the role of CD14, an LPS receptor, in stimulation of HGF by LPS. Cell surface CD14 antigen was not observed on HGF by flow cytometric analysis. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…One study showed that HGF express CD14 and that the LPS-induced signal transducing pathway is mediated by mCD14 (37). Another study found that HGF express CD14 neither on the surface nor in the mRNA and that ICAM-1 expression by HGF is up-regulated by serum-derived sCD14 (15). Our data support both sets of observations.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…One study showed that HGF express CD14 and that the LPS-induced signal transducing pathway is mediated by mCD14 (37). Another study found that HGF express CD14 neither on the surface nor in the mRNA and that ICAM-1 expression by HGF is up-regulated by serum-derived sCD14 (15). Our data support both sets of observations.…”
Section: Discussionsupporting
confidence: 86%
“…Watanabe et al (37) reported that HGF express mCD14 and that the LPS-induced signal-transducing pathway is mediated by mCD14. In contrast, Hayashi et al (15) found that HGF expressed CD14 neither on the surface nor in an mRNA analysis but were activated with LPS in a serum-derived sCD14dependent manner.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…A soluble form of CD14 (sCD14) lacking the glycosylphosphatidylinositol anchor is also present in serum (1), and sCD14 participates in the LPS-induced activation of endothelial and epithelial cells that normally do not express mCD14 (20). Hayashi et al (9) indicated that although human gingival fibro- blasts (HGF) expressed neither CD14 mRNA nor mCD14 on the cell surface, HGF were activated with LPS in a manner dependent on serum-derived sCD14 molecules. In contrast, Watanabe et al (36) reported mCD14 expression by HGF.…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al (9) reported that the induction of intercellular adhesion molecule 1 by LPS on human gingival fibroblasts is mediated by serum-derived sCD14. To clarify the participation of sCD14 in FBS in the enhanced production of VEGF by HPC stimulated with LPS, we added neutralizing anti-CD14 MAb MY4 to HPC cultures stimulated with LPS.…”
Section: Vegf Induction By Lps In Hpc Cultures As Shown Inmentioning
confidence: 99%